2019
DOI: 10.1002/suco.201900152
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial behavior between normal substrate and green ultra‐high‐performance fiber‐reinforced concrete under elevated temperatures

Abstract: This study assesses the effects of elevated temperatures (100, 200, 300, 400, and 500°C) on the bonding behavior of normal concrete (NC) substrate as old concrete and the new Green Universiti Sains Malaysia Reinforced Concrete (GUSMRC) as a repair material through slant shear, pull‐off, splitting tensile, and flexural tests. Sandblasting (SB) and grinding (GR) surface treatments were employed to enhance the bond strength of the NC/GUSMRC composite. The research also evaluates the mechanical characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 27 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Fig. 9 The relationship between splitting tensile strength and surface roughness of specimens at 200 ℃ and 500 ℃ after 28 days of water curing However, both CS and DS failed before the specified duration of the test when exposed to a temperature of 500 ℃, which is due to the development of thermal cracks on the composite surface and the decomposition of the concrete structure after exposure to high temperatures, physically and chemically, which begot spelling [15]. The splitting tensile strength of GS specimens experienced a decline of approximately 75%, which is deemed acceptable for withstanding the impact of such temperatures.…”
Section: Effect Of Elevated Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 9 The relationship between splitting tensile strength and surface roughness of specimens at 200 ℃ and 500 ℃ after 28 days of water curing However, both CS and DS failed before the specified duration of the test when exposed to a temperature of 500 ℃, which is due to the development of thermal cracks on the composite surface and the decomposition of the concrete structure after exposure to high temperatures, physically and chemically, which begot spelling [15]. The splitting tensile strength of GS specimens experienced a decline of approximately 75%, which is deemed acceptable for withstanding the impact of such temperatures.…”
Section: Effect Of Elevated Temperaturementioning
confidence: 99%
“…On the other hand, Sabah et al [15] conducted a retrospective study to investigate the composite action between UHPC and NC under fire exposure. The study employed various tests, including pull-off, flexure, splitting cylinder, and slant shear tests, to assess the bond strength between the two materials.…”
Section: Introductionmentioning
confidence: 99%
“…After 24 h at room temperature under moisture barrier, samples were demolded and submerged in a 25°C saturated lime water tank for 27 more days. Then bottom surfaces of specimens were dry sandblasted with 6 bar pressure from 150 mm distance with an average speed of 50 mm/s to expose the aggregate surfaces in order to remove cement paste layers and other impurities from the surface of the specimens 31–34 . One layer of unidirectional glass fabric was applied to the sandblasted surface using two‐part epoxy resin (with amine type hardener).…”
Section: Experimental Workmentioning
confidence: 99%
“…Then bottom surfaces of specimens were dry sandblasted with 6 bar pressure from 150 mm distance with an average speed of 50 mm/s to expose the aggregate surfaces in order to remove cement paste layers and other impurities from the surface of the specimens. [31][32][33][34] One layer of unidirectional glass fabric was applied to the sandblasted surface using two-part epoxy resin (with amine type hardener). The T g of the epoxy resin reported by the manufacturer was 45 C in normal curing temperature.…”
Section: Materials and Specimen Preparationmentioning
confidence: 99%
“…HSC with high strength and durability shows lower performance than normal strength concretes under high temperature effect 1,2 . Many previous studies have indicated that high temperature negatively affects the mechanical properties of HSC 2–5 and other concretes 6–18 . Schneider 19 demonstrated that the type of aggregate, heating and cooling down process and moisture content are parameters that influence most the mechanical properties of the concrete.…”
Section: Introductionmentioning
confidence: 98%